Tuning optical and electronic properties in novel carbazole photosensitizers for p-type dye-sensitized solar cells. (1st December 2018) - Carella, Antonio; Centore, Roberto; Borbone, Fabio; Toscanesi, Maria; Trifuoggi, Marco; Bella, Federico; Gerbaldi, Claudio; Galliano, Simone; Schiavo, Eduardo; Massaro, Arianna; Muñoz-García, Ana B.; Pavone, Michele
Abstract: This work reports the synthesis and characterization of three novel carbazole-based push-pull dyes that have been purposely designed to be applied in p-type dye-sensitized solar cells (DSSCs). By using the same electron-donor moiety (the carbazole group) and three different electron acceptor groups, we explore how these new substituents affect the optical and electrochemical properties of the dye. State-of-the-art theoretical characterization at the DFT and TD-DFT levels of theory provides the means to understand and elucidate the connection between the chemical composition, the structure and the electronic features of these dyes. The interface between the dyes and the prototypical p-DSSC electrode (i.e. NiO) is also investigated by first-principles calculations, highlighting the importance of taking into account the dye/electrode mutual polarization for a correct alignment of the relevant electronic states (e.g., dye HOMO and NiO valence band edge). Following these characterizations, preliminary studies on the photoelectrochemical performances of the new dyes in p-DSSCs provide promising results and motivate future investigations on these new systems.